Concentration of Heavy Metals Pb, Cr, and Hg in Demersal and Pelagic Fish in the Ciliwung River - Khoe Susanto Kusumahadi; Yeremiah Rubin Tjamin (Universitas Nasional Jakarta, 2022)
The objective of this research was to know the concentration of Pb, Cr, and Hg in Fish in the Ciliwung River. The observation of Heavy Metals concentration in Fish showed that only Hg in internal organ of Demersal Fish was significantly different according to the location and replication (P < 0.05), while Heavy Metals of Pb and Cr in Demersal and Pelagic Fish were not different according to the location and replication. It means that human activities such as industrial, settlement, agriculture and transportation along the Ciliwung River affect adsorption/absorption of Hg by Fish. Generally, Pb, Cr, and Hg concentration in the internal organ of Demersal and Pelagic Fish were higher than in the Fish Meat, because internal organ are the target organ of Heavy Metals substances in Fish. In general, metal concentrations of Pb, Cr, and Hg in the meat and organs of Demersal Fish were higher than that in the meat and organs of Pelagic Fish. This was due to the activity of Demersal Fish that forage and are active in bottom waters close to sources of heavy metal pollutants (sediment). The Result of observation show that in general, the contribution of human activities in the DKI Jakarta area to the presence of Pb, Cr, and Hg in the waters, sediment and Fish of the Ciliwung River was greater than in the Bogor and Depok areas.